Implementation of Flipped Classroom Learning Model Based Information and Communication Technology (ICT) to Improve Learning Outcomes - Huda, Nuril; Fitriani, Hanifah (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3205, 2024)
This study departed from the low student learning outcomes in the topic of mathematics subject comparison VII grade at MTs Almaarif 02 Singosari. From the initial analysis, only 62.5% of students could achieve the Criteria for Achievement of Learning Objectives (KKTP), while 37.5% of other students were not complete. This study aims to describe the implementation of a flipped classroom learning model based on ICT in improving student learning achievement. The research method applied is classroom action research (PTK: Penelitian Tindakan Kelas ) following the Kemmis and McTaggart model. The data collection tools used include learning outcome tests and student learning activity observation sheets. Data analysis techniques were carried out quantitatively with descriptive statistics to measure learning completeness and qualitative analysis through student activity observations. The results showed an increase in the percentage of students who achieved KKTP from 62.5% to 83.3%. Student learning activities also increased from 70.8% to 87.5%. Thus, the flipped classroom learning model based on ICT (Information and Communication Technology) is said to be effective in improving the learning outcomes of seventh-grade students at MTs Almaarif 02 Singosari on comparison material and becomes an alternative solution in improving the quality of learning in the classroom.